1991
DOI: 10.1111/j.1532-5415.1991.tb05930.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Strategies: An Overview of Criteria and Outcomes

Abstract: Researchers generally agree that Geriatric Evaluation and Management (GEM) Units are effective only when they are targeted at a specific group of frail, elderly patients who are most likely to benefit. Such patients are those who are neither too sick (eg, severely demented or moribund) nor too well. Various strategies for identifying such patients have been employed by investigators with little consensus on the most efficient targeting criteria. Criteria most often used for inclusion in GEM programs are variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 33 publications
2
54
0
2
Order By: Relevance
“…Prior to this, frailty has primarily been evaluated in hospitalized or nursing home populations (3,4,7,8,24,46,47). Such studies, due to the selection process by which their participants arrive in these settings, are likely to characterize persons with late-stage frailty, after the occurrence of related adverse outcomes, and having highly selected correlates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior to this, frailty has primarily been evaluated in hospitalized or nursing home populations (3,4,7,8,24,46,47). Such studies, due to the selection process by which their participants arrive in these settings, are likely to characterize persons with late-stage frailty, after the occurrence of related adverse outcomes, and having highly selected correlates.…”
Section: Discussionmentioning
confidence: 99%
“…Potential definitions of frailty abound, defining frailty as synonymous with disability (1,8,9), comorbidity (8), or advanced old age (3). Increasingly, geriatricians define frailty as a biologic syndrome of decreased reserve and resistance to stressors, resulting from cumulative declines across multiple physiologic systems, and causing vulnerability to adverse outcomes (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to produce sustained improvements in function is doubtful, but several studies have shown at least short term gains (Cohen, Feussner et al 2002). Careful patient selection is a critical factor in program effectiveness, with patients that are either too well, or severely ill (eg advanced dementia and terminal cancer) appearing to gain no benefit (Winograd 1991). Other success factors include the necessity for full decision-making control to rest with the geriatric team, and the ability to provide post-discharge follow-up (Reuben, Borok et al 1995).…”
Section: Enhancing Treatment Outcomesmentioning
confidence: 99%